2011
DOI: 10.1007/s11095-011-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles Enhance Adenovirus Transduction In Vitro and In Vivo

Abstract: The results showed that the combination of Magnetofection and Adenoviruses represents a promising strategy for gene therapy. Recently, a new integrated method to combine clinically approved magnetic cell isolation devices and genetic modification was developed. In this study, we validated that magnetic cell separation and adenoviral transduction can be accomplished in one reliable integrated and safe system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 70 publications
0
28
0
Order By: Relevance
“…These attributes of magnetic nanoparticles make them promising candidates to actively monitor the pharmacokinetics of therapeutics and can enhance delivery of therapeutics to target tissue. Recently, Sapet et al developed a magnetic nanoparticle-complexed Ad vector and showed accelerated vector accumulation at target sites under external MFG [114]. The Ad-magnetic hybrid system (Ad-MnMEIO) has been developed for gene delivery and concurrent MR imaging [115].…”
Section: Magnetic Field-mediated Local Delivery Of Viral Vectorsmentioning
confidence: 99%
“…These attributes of magnetic nanoparticles make them promising candidates to actively monitor the pharmacokinetics of therapeutics and can enhance delivery of therapeutics to target tissue. Recently, Sapet et al developed a magnetic nanoparticle-complexed Ad vector and showed accelerated vector accumulation at target sites under external MFG [114]. The Ad-magnetic hybrid system (Ad-MnMEIO) has been developed for gene delivery and concurrent MR imaging [115].…”
Section: Magnetic Field-mediated Local Delivery Of Viral Vectorsmentioning
confidence: 99%
“…To enhance transduction efficiency, viral surfaces are modified with cationic polymers and lipids via ionic interactions because the net charge of a viral particle surface is negative, approximately −20 mV [100-102], which is not preferable for facile interaction with anionic cellular surface. Adenoviruses have been complexed with commercial magnetic nanoparticles AdenoMag (OZ Biosciences) via electrostatic and hydrophobic interactions for magnetically-driven delivery, which showed significantly increased transduction for cells poorly expressing Coxsackie-adenovirus receptor (CAR) on cellular surface like NIH-3T3 cells (mouse fibroblast cells) [103]. Approximately 3.5-fold higher gene transfections were observed via magnetofection for NIH-3T3 cells compared with transfection without cationic polymer coated virus (polybrene-virus mixture).…”
Section: Applications Of Spion-based Delivery Systems For Biotheramentioning
confidence: 99%
“…The polymag™ particles (100–200 nm, OZ Biosciences, France) showed plasmid DNA delivery to NCI-H292 human lung epithelial cells 4-fold greater than the commercial lipid-based carrier, lipofectamine [32]. In addition, lipomag™ particles and Adenomag have been developed for gene delivery and virus delivery, respectively [89, 103]. The diverse fluidMAG particles (Chemicell) are magnetic nanoparticles coated with various polymers including chitosan, starch, and PVA, and lipids [84, 105].…”
Section: Commercialized Magnetic Nanoparticles For the Delivery Ofmentioning
confidence: 99%
“…The thermo-sensitive polymer will serve as a scaffold for MSCs, and spatiotemporal control of growth factor release will be achieved with genes triggered by exo genous signals (temperature, doxycycline) to direct cartilage and subchondral bone regeneration (49,50) . Alternatively, MSC can be transduced ex vivo by magnetofection (51,52) and then injected within the thermo-sensitive polymer into the damaged cartilage and activated as above.…”
Section: The Gene Vectorsmentioning
confidence: 99%
“…Alternatively an approach using magnetically enhanced adenoviral gene transfer to human MSC in monolayer culture has been successfully established using AdenoMag and the Viro-MICST infection method on a magnetic cell separation column (51,52) .…”
Section: Induction By Infl Ammationmentioning
confidence: 99%